Determinants of sorghum market dynamics: the case of Kuyu District, North Shoa Zone, Oromia Regional State, Ethiopia - Getachew Tulu (Discover Agriculture)
Abstract This study analyzed the market dynamics of sorghum in Ethiopia’s kuyu district, an area with significant production potential. Despite this, the understanding of sorghum market dynamics remains limited. The research aimed to identify key market actors and their roles, analyze market structure, conduct, and performance, determine factors influencing smallholder farmers’ sorghum market supply, and pinpoint major constraints and opportunities in the district’s production and marketing. Cross-sectional data from the 2021/22 production year were collected from 150 farm households, selected using a multiple-stage sampling technique, and from all 28 accessible sorghum traders. Data was obtained using pre-tested semi-structured questionnaires, focus group discussions for qualitative insights, and supplementary secondary sources. A double hurdle model was employed to analyze sorghum market participation, given that all sampled producers supplied to the market. Market participants included producers, rural and urban assemblers, wholesalers, and consumers. The market concentration ratio indicated a strongly oligopolistic structure in the Biriti market (50.86%). Econometric analysis revealed that education level, land allocation, lagged market price, sorghum yield, and access to credit positively impacted smallholder farmers’ market supply, while distance to the nearest market had a negative effect. Based on these findings, policy interventions are recommended to enhance capacity building (education), promote intensive land use, improve access to credit services, encourage farmer group marketing and linkages to exporters, increase sorghum yields, and develop road infrastructure.